2021
DOI: 10.1101/2021.11.12.467822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanistic insights into the enhancement or inhibition of phase separation by polyubiquitin chains of different lengths or linkages

Abstract: SummaryUbiquitin-binding shuttle UBQLN2 mediates crosstalk between proteasomal degradation and autophagy, likely via interactions with K48- and K63-linked polyubiquitin chains, respectively. UBQLN2 is recruited to stress granules in cells and undergoes liquid-liquid phase separation (LLPS) in vitro. However, interactions with ubiquitin or multivalent K48-linked chains eliminate LLPS. Here, we found that, although some polyubiquitin chain types (K11-Ub4 and K48-Ub4) did generally inhibit UBQLN2 LLPS, others (K6… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
(160 reference statements)
1
1
0
Order By: Relevance
“…Notably, they were the first to show that monovalent ligands destabilize phase separation driven by homotypic interactions, and the nonmonotonic behavior of ligands as a function of the ligand concentration was also anticipated and demonstrated (60,61). Very recently, Dao et al (62) found that the type of the polyubiquitin chain could also play distinct roles in the phase separation of UBQLN2, which further bolsters the general conceptual foundations of the findings from Ruff et al These results share some similarity with the dual effect of ATP (on the phase separation) reported here, which provides a key conceptual lynchpin for our current work. In general, this work well explains the nonmonotonic effect of ATP on the phase separation.…”
Section: Discussionsupporting
confidence: 85%
“…Notably, they were the first to show that monovalent ligands destabilize phase separation driven by homotypic interactions, and the nonmonotonic behavior of ligands as a function of the ligand concentration was also anticipated and demonstrated (60,61). Very recently, Dao et al (62) found that the type of the polyubiquitin chain could also play distinct roles in the phase separation of UBQLN2, which further bolsters the general conceptual foundations of the findings from Ruff et al These results share some similarity with the dual effect of ATP (on the phase separation) reported here, which provides a key conceptual lynchpin for our current work. In general, this work well explains the nonmonotonic effect of ATP on the phase separation.…”
Section: Discussionsupporting
confidence: 85%
“…The mechanisms of adsorption and wetting are distinct from the site-specific effects of ligands that are known to modulate driving forces for phase separation through preferential binding across phase boundaries 31, 32, 33, 34 . While preferential binding of ligands 35 can either compete against or add to extant interactions, thereby destabilizing or stabilizing condensates, adsorption of a ternary component has little effect on the interactions within a condensate 36 .…”
Section: Discussionmentioning
confidence: 99%